Art 1993 The Effectiveness of the Implementation of Law Number 16 of 2019 Amending Law Number 1 of 1974 on Marriage (A Study on Child Marriage Dispensation at the Religious Court of Palu City) : Islamic Family Law - salwa; Sidik; Suhri Hanafi (Al Mashaadir : Jurnal Ilmu Syariah, 2026)
Child marriage remains a significant social and legal issue in Indonesia, particularly after the enactment of Law Number 16 of 2019 concerning the Amendment to Law Number 1 of 1974 on Marriage, which raised the minimum marriage age to 19 years for both men and women. This study aims to analyze the implementation and effectiveness of the law in preventing child marriage through marriage dispensation cases at the Religious Court of Palu. This research employed an empirical juridical method using a qualitative approach. Data were obtained through interviews with the Vice Chairman and the Registrar of the Religious Court of Palu, documentation, and analysis of relevant laws and court decisions. The findings indicate that the implementation of Law Number 16 of 2019 has been carried out through stricter and more selective procedures in examining marriage dispensation applications. Judges not only consider administrative requirements, but also evaluate psychological readiness, educational continuity, economic conditions, and the best interests of the child in accordance with Supreme Court Regulation Number 5 of 2019 and child protection principles. However, the law has not been fully effective in reducing child marriage practices because marriage dispensation applications remain relatively high. Pregnancy outside marriage, low legal awareness, economic conditions, cultural acceptance of early marriage, and limited legal socialization are the dominant factors influencing the persistence of child marriage. Nevertheless, the amendment to the Marriage Law can be considered effective within judicial practice because judges have become more selective and cautious in granting marriage dispensations by prioritizing child protection and the best interests of the child.